Quantum interference effects in laser spectroscopy of muonic hydrogen, deuterium, and helium-3 - Amaro, Pedro (2015)
This research was supported in part by Fundacao para a Ciencia e a Tecnologia (FCT), Portugal, through Projects No. PEstOE/FIS/UI0303/2011 and No. PTDC/FIS/117606/2010, financed by the European Community Fund FEDER through the COMPETE. P.A. and J.M. acknowledge support from the FCT (Portugal), under Contracts No. SFRH/BPD/92329/2013 and No. SFRH/BD/52332/2013. B.F., J.J.K., M.D., and R.P. acknowledge support from the European Research Council (ERC) (Belgium) through StG. Grant No. 279765. F.F. acknowledges support from the Austrian Science Fund (FWF) (Austria) through START Grant No. Y 591-N16. L.S. acknowledges financial support from the People Programme (Marie Curie Actions) of the European Union's Seventh Framework Programme (FP7/2007-2013) (Belgium) under REA Grant Agreement No. 291734. A.A. acknowledges support from Swiss National Fond (SNF) (Switzerland) Grant No. 200020_159755. B.F. and R.P. would like to thank A. Beyer, L. Meisenbacher, and Th. Udem for illuminating discussions.